Pelatihan Pembelajaran Bahasa Inggris bagi Guru PAUD dan TK Se-kecamatan Karanganyar, Kabupaten Kebumen - Hastri Firharmawan; Alek Andika (Abdibaraya: Jurnal Pengabdian Masyarakat, 2022)
All teachers are demanded to create conducive learning environments in order to yield effective learning. However, there are many teachers who have drawbacks of knowledge on the use of teaching methods and media to achieve this demand. This community service entitles “Pelatihan Pembelajaran Bahasa Inggris bagi Guru PAUD dan TK Se-kecamatan Karanganyar, Kebumen”. It aims to give insights to kindergarten or early childhood school teachers in order to be able to identify learning methods and media which suit their students to improve learning effectiveness. This training was conducted from 9 to 11 January 2019 in Karanganyar, involving 20 kindergarten teachers. Lecturing and simulating methods were used to conduct the training. The results of the training shows that trainees are able to comprehend and identify learning methods and media to improve learning effectiveness. Besides, there are three methods to be assumed more effective to use to improve learning namely total physical response, suggestopedia, and communicative approach. Finally, English songs were considered the most suitable media to be applied for kindergarten or early childhood learners. Keywords: Learning, English, effective, methods